El pacto literario como lugar de encuentro - Pérez Esáin, Crisanto (Mercurio Peruano, 2013)
The author proposes, in this article, a series of considerations regarding the literary pact and its implicit dimension on discourse. To do so, he conducts a brief trail through the different literary theories of the 20th century until reaching pragmatics as a perspective of closeness to literary discourse. Valuing the previous contributions, he relates them to the notion of pact, and delimits them from similar notions, such as the contract one. Also, he applies the characteristics of the literary pact, implicit author and implicit reader, as protagonists of the different genres. He also offers possibilities for the application of these notions in the historic-literary, critical and didactic scope.
Keywords: literary pact, literary theory, Pragmatics, Narratology